Risk Factors of Osteoporosis and Post-Discharged Supplements and Drugs Intake in Patients with Lower Body Fractures - Nurul Izzah IBRAHIM; Mohd Sharkawi AHMAD; Mohamed S ZULFARINA; Sharifah Nurul Aqilah SAYED MOHD ZARIS; Nor Azlin ZAINAL ABIDIN; Isa Naina MOHAMED; Norazlina MOHAMED; Sabarul Afian MOKHTAR; Ahmad Nazrun SHUID (Tehran University of Medical Sciences, 2021)
No Abstract